EFFECTIVENESS OF APPLYING COFFEE GROUNDS ORGANIC FERTILIZER AND BOOSTER FERTILIZER ON THE GROWTH AND YIELD OF PURPLE EGGPLANT (Solanum melongena L.) - Irfandi Amir; Andi Bonewati; Sulkifli (Universitas Veteran Bangun Nusantara, 2026)
Increasing the national yield of purple eggplant (Solanum melongena L.) requires the application of environmentally friendly fertilization technology. This study was designed to evaluate the response of plants to the application of coffee grounds, organic waste, and booster fertilizer formulas, both applied separately and integrated, on the vegetative performance and fruit production of purple eggplant. The research method used a Randomized Block Design (RBD) with six treatments and three replications: K0 (control), K1 (20 g coffee grounds), K2 (2 ml/L booster), K3 (4 ml/L booster), K4 (20 g coffee grounds +2 ml/L booster), and K5 (20 g coffee grounds + 4 ml/L booster). The results showed that the K4 combination treatment produced the best harvest with the highest fruit weight of 277.08 g. Meanwhile, K5 exhibited the highest vegetative growth, as measured by plant height and leaf number. This fertilizer combination is effective in increasing the productivity of purple eggplant.